Image Processing Based Anomaly Detection Approach for Synchronous Movements in Cyber-Physical Systems - Yetis, Hasan; Karakose, Mehmet (Ieee, 2018)
Today cyber-physical systems are becoming more and more popular with the industry 4.0. Given the size and criticality of the systems they are used, it is very important that the cyber physical systems work properly. In this study, image-processing based anomaly movement detection method, which can be integrated to systems anytime, is proposed. With detection of anomaly movements and preventing unexpected situations, the cost arises from hitches, breakdowns or damaged productions is reduced. This study consists of two main section, first is implementing remote-controlled simple industrial robot system, second is the detection of unwanted movements and controlling the system.
23rd International Scientific-Professional Conference on Information Technology (IT) -- FEB 19-24, 2018 -- Zabljak, MONTENEGRO
Keywords: anomaly detection; cyber-physical systems; image processing; industry 4.0